Estágio supervisionado e PIBID na licenciatura em Letras-Inglês: vozes entrelaçadas coconstruindo o trabalho e a identidade docente sob a ótica do interacionismo sociodiscursivo - Araújo, Adriana da Silva (2021)
Initial language teacher education teachers in social spaces such as supervised internships and the Programa Institucional de Bolsas de Iniciação à docência - PIBID are fruitful fields for research on the work and construction of teacher identity based on the observation of how teachers interact with the constitutive objects of their work (AMIGUES, 2004). The interaction with these objects can generate conflicts and tensions that demand from teachers the elaboration of strategies to face them, which can be a source of development or constraints, especially for teachers in initial teacher education, a fact that motivated the interest in this qualitative research. (DENZIN and LINCONL, 2007) inserted in the area of Applied Linguistics. Based on this conception, this study has as general objective to investigate representations of teaching work and the identity construction constituted by an English language teacher in initial training as a student-teacher, a PIBID member and a teacher supervisor of internship at FAFIDAM. The specific objectives focus on: i. To identify the enunciative mechanisms that stand out in the texts/discourses of the teacher in training; ii. To investigate how the subjective world inscribes the representations of the teacher’s work and actions in the training spaces of PIBID and Internship IV; iii. To analyze what the main voices and modalizations signal about the identity construction of the teacher in initial training in the areas in which he works. The theoretical-methodological framework that guided this research focuses on Sociodiscursive Interactionism - ISD (BRONCKART, 1999, 2006b, 2008 and MACHADO and BRONCKART, 2009) aligned with the assumptions of the Clinic of Activity (CLOT, 2007; 2010; FAITA, 2004) and Ergonomics (AMIGUES, 2004, 2004; SAUJAT, 2004) and the conceptions on identity by Kleiman (1998), Moita Lopes (1998b), Bauman (2005) and Hall (2006). The analysis of forty-four selected excerpts from the corpus consisting of a reflective journal, an internship report, two questionnaires/interviews and two reflective sessions of an English language teacher in initial language teacher education in the PIBID and internship was conducted through the themes raised and of six thematic categories, four based on Amigues (2004) and two new ones identified in the texts/discourses. It was noticed with the analysis that the main voices that emerge in these texts/discourses are those of the empirical author who constantly position himself, mobilizing mainly appreciative and pragmatic modalizations to evaluate his work. These assessments, inserted in the subjective world, reveal reflections on the teacher's own actions in initial language teacher education, the actions of others and the constitutive objects with which he interacts. As a result, it is revealed that the teacher has multifaceted and fluctuating identities that alternate as the social spaces in Internship IV and PIBID vary, as well as the constitutive objects of his work in which social and intrapersonal factors have been added as they interfere in his activity. Finally, the analysis revealed that the conflicts and metamorphosis experienced by the collaborator are similar to those I experienced myself, so that such awareness is a source of development for me as a training teacher, as it enables the reorganization of my classroom environment.